Textbook of dementia care : an integrated approach - Jackson, Graham A.; Tolson, D. (Debbie) (Routledge, 2019)
Textbook of Dementia Care: An Integrated Approach gives an overview of dementia care at a level appropriate to health and social care students, as well as providing an update to experienced practitioners. Authors come from a variety of backgrounds including nursing, psychiatry, medicine, psychology and allied health professions. There is a good mix of content from experienced new authors, academics and practitioners. The book offers: acomprehensive list of contributors from different disciplines input from people living with dementia and their family carers relevant research to inform practice case examples to illustrate and inform the text. While directed primarily at a nursing and social care readership, the book also provides a readable general text appropriate for all involved in dementia care. It is written by expert practitioners in the field, many of whom are leaders in practice-based research. It incorporates the expertise of representatives of Alzheimer Scotland, but also includes accounts of people living with dementia, families, and carers, giving the reader a unique insight into the disease.